Avalição ecocardiográfica do ventrículo direito e da pressão arterial pulmonar em portadoresde hipertireoidismo - Gazzana, Maria Luiza [UNESP] (2014)
Background: Right ventricular (RV) dysfunction is an important determinant of prognosis in patients with pulmonary arterial hypertension (PAH) in many diseases. Nevertheless, the occurrence of PAH and RV dysfunction with their clinical manifestations in thyrotoxicosis patients without left ventricular dysfunction is not yet well understood. The aim of the present study was to evaluate by echocardiography, the cardiac structural and functional parameters, particularly the right side of the heart, and to evaluate their correlation with clinical and laboratorial findings, before and after medical therapy for thyrotoxicosis. Methods: In this prospective study, 32 patients, both genders, and 18 to 80 years old with primary hyperthyroidism caused by diffuse goiter (Graves' disease), nodular goiter (Plummer's disease), or multinodular goiter were evaluated. Patients were submitted to clinical, laboratorial, and echocardiographic assessments. Echocardiographic examination focused the right heart using standard techniques, such as mono (uni-) and two-dimensional assessments and pulsed and tissular Doppler. In 26 patients the exam was repeated after normalization of hyperthyroidism. Results: Patients were 42.5±11.9 years old, most females (90.6%), and Graves' disease was the most frequent etiology (75%). Fifteen (46.9%) were classified as class I and 17 (53.1%) as class II of New York Heart Association functional classification. The prevalence of PAH, defined as pulmonary artery systolic pressure (PASP) ≥36 mmHg, in untreated hyperthyroidism patients was 43.8%. PAH patients showed a trend to higher frequency of dyspnea than patients with normal PASP (71.4% vs. 38.9%, p=0.067). Free T4 (FT4) was greater in PAH patients than in patients with normal PASP and correlated positively with PASP (r=0.42, p<0.05). There was a trend to correlation between pulmonary vascular resistance and PASP (r=0.32, p=0.073). Twelve patients (37.5%) had impaired ...